Plaque and gingivitis in the elderly: a randomized, singleblind clinical trial on the outcome of intensified mechanical or antibacterial oral hygiene measures - Ulrich Schiffner, (Blackwell Synergy, 2007)
Objectives: To study the outcome of intensified mechanical oral hygiene compared with the effect of an adjunctive antibacterial mouth rinse on plaque and gingivitis in elderly people. Material and Methods: In a randomized, single-blind, 6-month controlled clinical study, 106 subjects, 55 years or older, were divided into four groups: (I) Participants were instructed on improved mechanical oral hygiene, including interdental hygiene; (II) subjects used an antibacterial mouth rinse containing amine and stannous fluoride in addition to their usual oral hygiene practices; (III) both intensive mechanical and antibacterial measures were combined; and (IV) a control group with no specific regimen. Gingivitis and plaque were examined. Results: After 6 months, both plaque and gingivitis scores were significantly lower than at baseline in all groups. Reductions in gingivitis differed significantly between the control group and all other groups but not between the three intervention groups. Only groups with improved mechanical oral hygiene showed significant improvements in plaque scores compared with control. Conclusions: Intensive mechanical oral hygiene resulted in greater plaque reduction than the combination of an antibacterial rinse and usual oral hygiene procedures. Gingivitis was reduced by both intensive oral hygiene and use of the amine/stannous fluoride rinse. Combining intensive mechanical oral hygiene with the antibacterial rinse did not result in further gingivitis reduction.